2011
DOI: 10.1016/j.ejso.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach in the treatment of patients with small cell bladder carcinoma

Abstract: Small cell carcinoma of the urinary bladder (SCCUB) is considered to be a tumor with a neuroendocrine phenotype characterised by aggressive behaviour and poor prognosis. Small cell carcinoma of the urinary bladder comprises 0,35 to 1% of all bladder cancers and is frequently observed in combination with other histological subtypes of carcinoma. Clinical presentation is characterized by advanced stage at diagnosis and rapidly progressive disease. In daily clinical practice there is no gold standard for the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Le taux de survie globale à cinq ans tous stades confondus est de 19% (16 à 25%). Le pronostic des carcinomes neuroendocrines purs semble être plus défavorable que celui des formes mixtes (9,5 contre 34 mois) [3, 6, 14]. …”
Section: Discussionunclassified
“…Le taux de survie globale à cinq ans tous stades confondus est de 19% (16 à 25%). Le pronostic des carcinomes neuroendocrines purs semble être plus défavorable que celui des formes mixtes (9,5 contre 34 mois) [3, 6, 14]. …”
Section: Discussionunclassified
“…Early diagnosis of the disease as well as surgery, neoadjuvant, adjuvant, or palliative chemotherapy with or without radiotherapy are the cornerstones of patient care (13,(48)(49)(50). Details about prognosis and therapy are shown in Table III (13,23,35,41,42,44,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60).…”
Section: Neuroendocrine Tumors Of the Urinary Bladdermentioning
confidence: 99%
“…The MDACC trial [22] reported 78% of cancer-specific survival in 21 patients treated with chemotherapy plus radical cystectomy. Radiation therapy is applied as a local treatment with a similar result to surgery following a platinum-based chemotherapy with 56-70 Gy [23] . In a study of 15 patients treated with radiation therapy plus chemotherapy there is evidence of a complete response in 88% and a median overall survival of 32.5 months [24] .…”
Section: Discussionmentioning
confidence: 99%